AN ANALYSIS OF EIGHTH-GRADE STUDENTS’ ERRORS IN SOLVING PYTHAGOREAN THEOREM PROBLEMS BASED ON NEWMAN’S ERROR ANALYSIS - Fitra Angraina; Muh. Hasbi; Alfisyahra Alfisyahra; Sukayasa Sukayasa (JME (Journal of Mathematics Education), 2026)
This study aims to describe students’ errors in solving Pythagorean theorem problems based on Newman’s Error Analysis (NEA). This study employed a qualitative descriptive approach. The subjects consisted of two eighth-grade students of SMP Negeri 1 Banawa Tengah selected through written tests and interviews. The results show that both students made errors at several stages of NEA, with one student committing more errors than the other. The dominant errors occurred at the comprehension, transformation, and process skill stages. These errors were caused by limited conceptual understanding of the Pythagorean theorem, carelessness in calculations, and haste in answering the questions. The findings of this study provide insights for improving mathematics instruction, particularly in strengthening students’ conceptual understanding and problem-solving skills.